Spectrum-Effect Relationships Between the Bioactive Ingredient of Syringa oblata Lindl. Leaves and Its Role in Inhibiting the Biofilm Formation of Streptococcus suis - Liu, Yan-Yan; Chen, Xing-Ru; Gao, Ling-Fei; Chen, Mo; Cui, Wen-Qiang; Ding, Wen-Ya; Chen, Xue-Ying; God’spower, Bello-Onaghise; Li, Yan-Hua (Frontiers in Pharmacology, 2018)
Syringa oblata Lindl. (S. oblata) has been used in herbal medicines for treating bacterial diseases. It is also thought to inhibit Streptococcus suis (S. suis) biofilm formation. However, due to the inherent nature of the complexity in its chemical properties, it is difficult to understand the possible bioactive ingredients of S. oblata. The spectrum-effect relationships method was applied to screen the main active ingredients in S. oblata obtained from Heilongjiang Province based on gray relational analysis. The results revealed that Sub-MICs obtained from ten batches of S. oblata could inhibit biofilm formation by S. suis. Gray relational analysis revealed variations in the contents of 15 main peaks and rutin was discovered to be the main active ingredient. Then, the function of rutin was further verified by inhibiting S. suis biofilm formation using crystal violet staining. Computational studies revealed that rutin may target the chloramphenicol acetyltransferase protein in the biofilm formation of S. suis. In conclusion, this study revealed that the spectrum-effect relationships and computational studies are useful tools to associate the active ingredient with the potential anti-biofilm effects of S. oblata. Here, our findings would provide foundation for the further understanding of the mechanism of S. oblata intervention in biofilm formation.